The features of communication in social work in the convention of the Сovid-19 pandemic - Плахова, О. М.; Карчова, О. М. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2021)
The article presents the study of communication as a way of interpersonal and intergroup interaction, as a source of human activity, which is manifested in the search for information, communication of their thoughts, experiences and ways to communicate for help. The role of social communication in modern society is studied. The article emphasizes the growing role of social work in crisis situations in society as a resource that contains timely, professional, reliable information. The article presents information how the communicative process has changed within social work in the context of the Covid-19 pandemic: the transition to remote communication, the emergence of new «pandemic» functions in the activities of specialists, the emergence of new and exacerbation of old social problems. Statistics are provided on social workers who work in an enhanced mode during the quarantine period for the provision of social services (material, psychological, legal aid) to clients. These are especially client groups such as the elderly, war and labor veterans, people with special needs, children and other vulnerable groups. The authors draw attention to the fact that under conditions of quarantine restrictions, some traditional sources of communication have lost their effectiveness and relevance, however, the need for information has increased significantly. There are several areas of communicative interaction, which are becoming increasingly relevant in social work: the creation of online communities, on-line paperwork, on-line consultations, training, supervision and others.